Chapter In te compositae mihi fixa sit anchora vitae: autobiografia (e agiografia) nei Natalicia di Paolino di Nola - Lubian, Francesco (Firenze University Press, 2025)
This paper examines the link between autobiographical discourse and hagiographic poetry in Paulinus of Nola's Natalicia, showing Paulinus as the unifying force of the poetic discourse, with his relationship to Saint Felix shaping his identity. In Natalicia 1 and 2, Paulinus reconnects with Felix after a long journey, while in Natalicium 13, he highlights Felix’s pivotal role in his life, presenting himself as the saint’s spiritual heir. In Natalicia 4 and 5, Felix’s biography subtly shifts into Paulinus’ autobiography, turning the Acta Felicis into a medium for self-representation. This reveals the complexity of self-narrative in late antique Latin poetry.